Tracheal or bronchial wedge resection: Case report - Jiao, Zhenhua; Tang, Zhe; Yu, Jun (Frontiers in Surgery, 2023)
Background: Primary tracheal or bronchial tumors are relatively uncommon, whether benign or malignant. Sleeve resection is an excellent surgical technique for most primary tracheal or bronchial tumors. However, depending on the size and location of the tumor, tracheal or bronchial wedge resection can be performed with the assistance of a fiberoptic bronchoscope for some malignant and benign tumors. Case Description: we performed a single incision video-assisted bronchial wedge resection in a patient with a left main bronchial hamartoma with a size of 7 * 5 * 5 mm. The patient was discharged from the hospital six days after the surgery with no postoperative complications. There was no obvious discomfort during the 6-month postoperative follow-up, and the reexamination of fiberoptic bronchoscopy revealed no evident stenosis of the incision. Conclusions: Through the detailed case study and literature review, we believe that tracheal or bronchial wedge resection is a significantly superior technique under the appropriate conditions.